The Study on Food Consumption Patttern and Nutritional Status of Adolescence in Public Senior High School 1 Eban - Kono, Maria Emelinda Olga; Nur, Marselinus Laga; Boeky, Daniela L. A.; Talahatu, Anna (Timorese Journal of Public Health, 2021)
Many variables, both directly and indirectly impact teenage girls' eating habits and nutritional condition. The goal of this study is to see if there's a link between teenage girls' nutritional awareness, their mothers' education, their parents' roles, and their family's income and their eating habits and nutritional status in SMA Negeri 1 Eban. This study utilized an analytic survey with a cross-sectional research design to evaluate the eating habits and nutritional status of teenage girls in SMA Negeri 1 Eban over a limited period of time. Participants in this study were all young women in grades X and XI, amounting to 262 people. The sample method was used by simple random sampling. The results of the research revealed that there was a significant relationship between nutritional knowledge (p = 0.010) and the nutritional status of adolescent girls. The research also stated that there was no significant relationship between nutritional knowledge (p = 0.887), maternal education (p = 0.746), parental roles (p = 0.745), and family income (p = 0.078) with the consumption patterns of adolescent girls. and there was no significant relationship between mother's education (p = 0.439), the role of parents (p = 0.396), and family income (p = 0.075). For young women, this research is intended to provide an overview of consumption patterns and nutritional status, enable them to change bad eating habits at home and at school, and apply nutritional information in their daily lives.